2020
DOI: 10.1007/s00415-020-10094-0
|View full text |Cite
|
Sign up to set email alerts
|

The specific pattern of retinal nerve fiber layer thinning in Parkinson’s disease: a systematic review and meta-analysis

Abstract: Background and purposeThe peripapillar nerve fiber layer (pRNFL) thinning in different retinal quadrants or sectors remains controversy. We conducted a systematic review and meta-analysis on the pattern of pRNFL thinning in Parkinson's disease (PD) patients to provide a biomarker for PD differential diagnosis. Methods We systematically searched PubMed and EMBASE to identify studies comparing pRNFL thickness in PD patients and health controls using spectral domain-optical coherence tomography from inception to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
2
17
0
1
Order By: Relevance
“…Two recent reviews and meta-analyses have reported a thinning of the inner retinal layers and the pRNFL as prominent features in the eyes of Parkinson's patients. 17,18 Other groups also found significant thinning of pRNFL in PD compared to HC, 17,19,20 however the authors pointed out that their analysis gathered results from patients with different stages of Parkinson's disease. We found no significant difference in the pRNFL thickness between patients with PD and HC (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Two recent reviews and meta-analyses have reported a thinning of the inner retinal layers and the pRNFL as prominent features in the eyes of Parkinson's patients. 17,18 Other groups also found significant thinning of pRNFL in PD compared to HC, 17,19,20 however the authors pointed out that their analysis gathered results from patients with different stages of Parkinson's disease. We found no significant difference in the pRNFL thickness between patients with PD and HC (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Huang et al [16] performed a Meta-analysis of pRNFL thickness in PD patients and the results showed that the thickness of pRNFL decreased globally in four quadrants. The degree of pRNFL thinning was larger in the inferior quadrant than that in superior quadrant and larger in the temporal quadrant than that in the nasal quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…Responding to the rapidly expanding body of research linking ocular pathology and AD brain lesions, the American Alzheimer’s Association convened a ‘think tank’ in mid-2019 aimed at establishing the foundations for population-based detection and monitoring of mild cognitive impairment and AD [ 37 ]. Other disorders for which retinal imaging is being explored as a screening/prognostic tool include Parkinson’s disease [ 20 ], psychiatric diseases including schizophrenia, bipolar disorder and major depressive disorder [ 39 ] and multiple sclerosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%